Antiphospholipid antibodies mediate autoimmunity against dying cells. (August 2013) - Andreoli, Laura; Fredi, Micaela; Nalli, Cecilia; Franceschini, Franco; Meroni, Pier Luigi; Tincani, Angela
<x xml:space="preserve">Abstract</x> The Antiphospholipid Syndrome (APS) is characterized by thrombosis and pregnancy loss, clinical events mediated by pathogenic anti-phospholipid autoantibodies (aPL). β2-glycoprotein I (β2GPI) is the major autoantigens recognized by aPL. β2GPI is a cationic protein that binds to negatively charged surfaces such as those of apoptotic cells. This feature may lead to two major events: i) immunization with β2GPI fosters the Fc-receptor-mediated uptake by antigen presenting cells of apoptotic material decorated with β2GPIand the activation ofβ2GPI-specific T cells which in turn provide help to β2GPI-specific B cells for the production of anti-β2GPI; ii) apoptotic bodies decorated with β2GPI can be opsonized by anti-β2GPI and shifted towards a pro-inflammatory clearance by macrophages; epitope spread can occur with the generation of autoimmunity against nuclear autoantigens. In the presence of a predisposing genetic background and of a particular cytokine environment (type I interferons), the sequential emergence of autoantibodies can evolve into overt clinical disease. The spectrum of clinical phenotypes of the patients can be modulated by several factors affecting the pathogenicity of anti-β2GPI (e.g. domain specificity). We conclude that dying cells may play a dual role in APS: (I) as immunogen for the induction of aPL (etiology) and (II) as targets of aPL for the chronification of inflammation and the development of autoimmune diseases (pathology).